1996
DOI: 10.1111/j.1746-1561.1996.tb03414.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief Nurse Consultations for Preventing Alcohol Use Among Urban School Youth

Abstract: This study examined the effects of brief nurse consultations in preventing alcohol use among inner-city youth. Participants included 138 sixth-eighth grade students attending an inner-city public school in Jacksonville, Florida. Subjects were randomly assigned by computer to either the intervention (STARS program) or a control group. Baseline and three-month post-tests were conducted at the target school site. A significant difference was found on heavy alcohol use with intervention subjects showing a reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
1
29
0
1
Order By: Relevance
“…This included two systematic reviews (Tilley andChambers, 2003, Wainwright et al, 2000), nine RCTs (Cameron et al, 1999, DeLago et al, 2001, Harrell et al, 1998, Hill et al, 1991, Lamb et al, 1998, Persaud et al, 1996, Puskar et al, 2003, Werch et al, 1996, Werch et al, 2003, one quasi RCT where allocation was by coin toss (Pike and Banoub-Baddour, 1991) and four non-randomised controlled trials (Allen, 2003, Long et al, 1975, Munodawafa et al, 1995, Skybo and Ryan-Wenger, 2002). …”
Section: Current Evidence Base For School Nursing Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This included two systematic reviews (Tilley andChambers, 2003, Wainwright et al, 2000), nine RCTs (Cameron et al, 1999, DeLago et al, 2001, Harrell et al, 1998, Hill et al, 1991, Lamb et al, 1998, Persaud et al, 1996, Puskar et al, 2003, Werch et al, 1996, Werch et al, 2003, one quasi RCT where allocation was by coin toss (Pike and Banoub-Baddour, 1991) and four non-randomised controlled trials (Allen, 2003, Long et al, 1975, Munodawafa et al, 1995, Skybo and Ryan-Wenger, 2002). …”
Section: Current Evidence Base For School Nursing Interventionsmentioning
confidence: 99%
“…Ten studies were done in the USA (Allen 2003, DeLago 2001, Harrell 1998, Lamb 1998, Long 1975, Puskar 2003, Persaud 1996, Skybo 2002, Werch 1996, Werch 2003, two in Canada (Cameron et al, 1999, Pike andBanoub-Baddour, 1991), one in the UK (Hill et al, 1991) and one in Zimbabwe (Munodawafa 1995). Neither of the systematic reviews found any studies that met their inclusion criteria.…”
Section: Current Evidence Base For School Nursing Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reason for exclusion Baer et al [46] Brief intervention: mean age 21.2 Baer et al [33] 4-year follow-up: results not directly comparable with 2-year data [22] Botvin et al [47] Group intervention Breslin et al [48] Individual assessment + 4 group sessions D'Amico & Fromme [49] Group intervention based in school D'Amico & Fromme [50] Group intervention based in school Deas et al [51] HIV/AIDS risk behaviours Dimeff & McNeely [52] Computer + motivational intervention: mean age 21.2 Dunn & Ries [53] Brief intervention: general hospital sample Jamrozik & Tait [54] Brief intervention: measured attitudinal change Roberts et al [55] Re-analysis of Marlatt data [22] Saunders et al [56] Brief intervention plus pharmacotherapy, mean age 28 Snow et al [57] Classroom-based intervention Spoth et al [58] Multi-session intervention Stevens et al [59] Brief intervention: mean age 4 20 Werch et al [35] Brief intervention, classroom-based intervention, plus six follow-up interventions Werch et al [34] Brief intervention plus up to nine home-based exercises…”
Section: Appendix 1 Studies Excluded From the Review And The Reason mentioning
confidence: 99%
“…Finalmente, intervenciones desarrolladas en estudiantes en donde se involucra la atención directa del profesional de la salud, con población específica en alguna etapa de adquisición y con abordaje de factores de protección, favorecen la resistencia del adolescente al consumo de drogas, y existe evidencia de reducciones de corto plazo en el consumo de alcohol cuando se imparten sesiones educativas comparado con intervenciones en donde se brinda solo material impreso (10)(11)(12) . Estudios realizados en Monterrey indican que una gran parte de los jóvenes se encuentran en la etapa de adquisición precontemplación al consumo de tabaco y alcohol, por lo que la prevención primaria específica a la etapa de precontemplación es importante para evitar el inicio al consumo de sustancias.…”
Section: Introductionunclassified